Preparation method of optical-grade scandium metaphosphate

By preparing high-purity scandium carbonate and scandium dihydrogen phosphate, the problem of the lack of industrial preparation of scandium metaphosphate in China has been solved, the industrial production of high-purity optical grade scandium metaphosphate has been achieved, and the performance of optical glass has been improved.

CN119349528AInactive Publication Date: 2025-01-24CIXIAN XINYU OPTOELECTRONICS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411490077.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There is a lack of industrial preparation methods for scandium metaphosphate in China, which affects the optimization of optical glass performance.

Method used

By preparing high-purity scandium carbonate and scandium dihydrogen phosphate, and using specific solution dilution, filtration, recrystallization and high-temperature treatment steps, optical grade scandium metaphosphate with a purity of more than 99.9% was successfully prepared.

Benefits of technology

The industrialized production of high -purity optical phosphate is achieved, the requirements for the use of optical glass firing, and improved the diversity and superiority of optical glass performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349528A_ABST
    Figure CN119349528A_ABST
Patent Text Reader

Abstract

In order to solve the technical problem that an industrial preparation method of scandium metaphosphate is lacked in China at present, the invention provides a preparation method of optical-grade scandium metaphosphate, and the optical-grade scandium metaphosphate with the purity reaching 99.9% or above can be produced. The method comprises the following steps: dissolving scandium chloride hexahydrate by using a hydrochloric acid solution to obtain a scandium chloride solution, filtering and recrystallizing to obtain scandium chloride hexahydrate crystals, and reacting the scandium chloride hexahydrate crystals with an ammonium carbonate solution to obtain high-purity scandium carbonate; then, the diluted food-grade phosphoric acid and the high-purity scandium carbonate are subjected to a heat preservation stirring reaction, scandium dihydrogen phosphate crystals are obtained, the scandium dihydrogen phosphate crystals are subjected to low-temperature drying foaming treatment and high-temperature treatment, and scandium metaphosphate is obtained. According to the method, the optical-grade scandium metaphosphate with the purity reaching 99.9% or above can be industrially produced, and the use requirement of optical glass firing is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing scandium metaphosphate. Background Art

[0002] Scandium metaphosphate, as an additive for optical glass, plays a special role in adjusting the transmittance and refractive index of optical glass. At present, Japan and Germany are experimenting with what proportion of scandium metaphosphate can be added to obtain glass with better performance. Once the experiment is successful, the performance of optical glass will be more diverse and have excellent prospects. However, there is no public preparation method of scandium metaphosphate in China. Summary of the invention

[0003] In order to solve the technical problem of the lack of industrial preparation methods for scandium metaphosphate in China, the present invention proposes a preparation method for optical grade scandium metaphosphate, which can produce optical grade scandium metaphosphate with a purity of more than 99.9%.

[0004] The technical solution of the present invention is:

[0005] A method for preparing optical grade scandium metaphosphate, which is special in that it comprises the following steps:

[0006] Step 1, preparing high-purity scandium carbonate;

[0007] Step 1.1: dilute analytically pure hydrochloric acid with pure water / high-purity water to a hydrochloric acid solution with a mass fraction of 10-15%, and then add scandium chloride hexahydrate thereto for dissolution, wherein the mass ratio of the hydrochloric acid solution to the scandium chloride hexahydrate is 4-6:1, to obtain a scandium chloride solution; when the scandium chloride is dissolved in the hydrochloric acid solution, it will be partially hydrolyzed into scandium chloride hydrate and cannot be completely dissolved. The present invention dilutes the analytically pure hydrochloric acid to a mass fraction of 10-15%, which can ensure that the scandium chloride is dissolved transparently, while taking into account the dissolution rate of the scandium chloride and the loss of hydrochloric acid.

[0008] Step 1.2: filtering the scandium chloride solution to remove insoluble matter and mechanical impurities to obtain a relatively pure scandium chloride solution;

[0009] Step 1.3: The scandium chloride solution obtained in step 1.2 is recrystallized to control the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.2 ppm, thereby obtaining scandium chloride hexahydrate crystals; since the rare earth elements in the refined scandium chloride have been processed relatively cleanly, the recrystallization in this step only needs to remove the excessive metal impurities;

[0010] Step 1.4: dissolving analytically pure ammonium carbonate with pure water / high-purity water to form an ammonium carbonate solution with a mass fraction of 15-18% (a mass fraction that is too high will cause the subsequent synthesis of scandium carbonate to be too viscous and not conducive to operation, and a mass fraction that is too low will cause the subsequent synthesis of scandium carbonate to have a low production capacity), filtering, and controlling the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the ammonium carbonate solution to be less than 0.2 ppm;

[0011] Step 1.5: After the scandium chloride hexahydrate crystals obtained in step 1.3 are dissolved in pure water / high-purity water to form a scandium chloride solution with a mass fraction of 15-18% (too high a mass fraction will cause the subsequently synthesized scandium carbonate to be too viscous and not conducive to operation, and too low a mass fraction will cause the subsequent synthesis of scandium carbonate to have a low production capacity), the solution is slowly added to the ammonium carbonate solution obtained in step 1.4 under stirring, and then heat-insulated, aged, filtered, and washed with water. The chlorine content is controlled to be less than 50ppm, and the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium are all less than 0.5ppm, to obtain active high-purity scandium carbonate;

[0012] Step 2, preparing scandium metaphosphate;

[0013] Step 2.1: using food-grade phosphoric acid with a mass fraction of 20-25% (this mass fraction range is convenient for synthesizing scandium dihydrogen phosphate and can take into account production capacity) and the active high-purity scandium carbonate to react with heat preservation and stirring, concentrating and crystallizing, filtering, and obtaining scandium dihydrogen phosphate crystals; the scandium dihydrogen phosphate crystals obtained in this step are only crystals with the same components as scandium dihydrogen phosphate, and are not complete scandium dihydrogen phosphate crystals;

[0014] Step 2.2: Dry the scandium dihydrogen phosphate crystals at 200-250°C, and foaming will occur during the drying period. When the foaming hardens, continue to dry at 200-250°C for 1-2 hours, then heat the foamed scandium dihydrogen phosphate to 500-600°C, and treat at high temperature for 2-3 hours to fully dehydrate, and obtain the target product. After XRD detection, the product is qualitatively scandium metaphosphate; after testing, the content of transition metal elements such as cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the product is less than 1ppm, the loss on ignition is less than 0.5%, the content of phosphorus pentoxide is 75-76%, the content of scandium oxide is 24-25%, and the purity is greater than 99.9%. Due to the special properties of scandium metaphosphate, this step must go through a 200-250°C front drying process, which we call foaming treatment, otherwise there will be serious sticking to the disc in the later stage, and the material cannot be removed.

[0015] Furthermore, in step 1.2, the scandium chloride solution is filtered using a filter with a filtration accuracy of at least 1 μm.

[0016] Furthermore, the specific method of step 1.3 is: heating the scandium chloride solution obtained in step 1.2 to 110-120°C for concentrated crystallization, stopping heating when more crystals appear, stirring and cooling to crystallize, and when the temperature drops to 30-40°C, standing for 30-60 minutes and then filtering, and the iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium contents are all controlled to be less than 0.2ppm, to obtain scandium chloride hexahydrate crystals.

[0017] Furthermore, in step 1.5, the mixture is kept warm at 70-80° C. and stirred for aging for 1-2 hours.

[0018] Furthermore, step 2.1 is specifically as follows: diluting food-grade phosphoric acid with pure water / high-purity water to a mass fraction of 20-25%, and then adding the active high-purity scandium carbonate thereto, the molar ratio of phosphoric acid to scandium carbonate is 3.1-3.5:1 (if it is not within this range, it will lead to incomplete reaction or waste of phosphoric acid), stirring and reacting at 60-80°C for 30-60 minutes, then heating to 110-120°C for concentrated crystallization, stopping heating when sugar-like crystals appear, continuing to stir and cool to crystallize, cooling to 30-40°C, standing until the ratio of supernatant to crystals is 1:8-10, filtering, and obtaining dihydrogen phosphate scandium crystals.

[0019] The present invention also provides an optical grade scandium metaphosphate, which is special in that it is prepared by the above method.

[0020] The present invention also provides an optical glass, which is special in that the optical grade scandium metaphosphate is used as an additive.

[0021] The advantages of the present invention are:

[0022] The invention can industrially produce optical-grade scandium metaphosphate with a purity of more than 99.9%, meeting the use requirements of optical glass firing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the XRD diagram of the scandium metaphosphate prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] Reaction equation of the present invention:

[0025] 2ScCl3+3(NH4)2CO3====Sc2(CO3)3+6NH4Cl

[0026] Sc2(CO3)3+6H3PO4====2Sc(H2PO4)3+6CO2+3H2O

[0027] Sc(H2PO4)3====Sc(PO3)3+3H2O

[0028] The present invention is further described in detail below by way of examples.

[0029] Example 1

[0030] In this embodiment, scandium metaphosphate is prepared by the following steps

[0031] Step 1, preparing active scandium salt;

[0032] Step 1.1: Take analytical pure hydrochloric acid and place it in a glass beaker, add high-purity water to dilute it into a hydrochloric acid solution with a mass fraction of 10%, and then add scandium chloride hexahydrate to the diluted hydrochloric acid solution to dissolve it. The mass ratio of the hydrochloric acid solution to the scandium chloride hexahydrate is 5:1, and a scandium chloride solution is obtained;

[0033] Step 1.2: filtering the scandium chloride solution through a filter with a precision of 1 μm to remove insoluble matter and mechanical impurities therein to obtain a relatively pure scandium chloride solution;

[0034] Step 1.3: The scandium chloride solution obtained in step 1.2 is heated to 116° C. for concentrated crystallization. When more crystals appear, heating is stopped, and the solution is stirred and cooled for crystallization. When the temperature drops to 36° C., the solution is allowed to stand for 30 minutes and then filtered. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, and scandium chloride hexahydrate crystals are obtained.

[0035] Step 1.4: Take analytical pure ammonium carbonate and add high-purity water to dissolve it. After dissolving to a mass fraction of 15.9%, filter it and control the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.2ppm to obtain an ammonium carbonate solution for standby use.

[0036] Step 1.5: After dissolving the scandium chloride hexahydrate crystals obtained in step 1.3 into a scandium chloride solution with a mass fraction of 16.1% with high-purity water, slowly add the solution to the ammonium carbonate solution obtained in step 1.4 under stirring, keep warm and stir at 70° C. for 1.5 hours, filter, wash with water, control the chlorine content to less than 50 ppm, and the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to less than 0.5 ppm, to obtain active high-purity scandium carbonate;

[0037] Step 2, preparing scandium metaphosphate;

[0038] Step 2.1 Take food-grade phosphoric acid, add high-purity water to dilute it to a mass fraction of 20%, add the high-purity scandium carbonate obtained in step 1.5, the molar ratio of phosphoric acid to scandium carbonate is 3.1:1, heat to 70°C for insulation reaction for 30 minutes, then heat to 110°C for concentration and crystallization, stop heating when concentrating to sugar-like crystals, continue stirring to cool and crystallize, cool to 33°C, and then stand for about 30 minutes, at which time the ratio of supernatant to crystals is 1:8-10, filter to obtain scandium dihydrogen phosphate crystals;

[0039] Step 2.2 Add the scandium dihydrogen phosphate crystals obtained in step 2.1 to a tetrafluoro beaker and dry at 200°C. Foaming will occur during the drying period. When the foaming hardens, continue to dry at 200°C for 2 hours. Add the foamed scandium dihydrogen phosphate to a quartz crucible and heat it to 550°C for high-temperature treatment for 2.5 hours. The iron content in the center is 1.6ppm, and the target product is obtained. XRD detection is qualitatively scandium metaphosphate. After testing, the content of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the product is less than 1ppm, the loss on ignition is 0.44%, and the purity is greater than 99.9%.

[0040] Example 2

[0041] In this embodiment, scandium metaphosphate is prepared by the following steps

[0042] Step 1, preparing active scandium salt;

[0043] Step 1.1: Take analytical pure hydrochloric acid and place it in a glass beaker, add high-purity water to dilute it into a hydrochloric acid solution with a mass fraction of 15%, and then add scandium chloride hexahydrate to the diluted hydrochloric acid solution to dissolve it. The mass ratio of the hydrochloric acid solution to the scandium chloride hexahydrate is 5.5:1, and a scandium chloride solution is obtained;

[0044] Step 1.2: filtering the scandium chloride solution through a filter with a precision of 1 μm to remove insoluble matter and mechanical impurities therein to obtain a relatively pure scandium chloride solution;

[0045] Step 1.3: The scandium chloride solution obtained in step 1.2 is heated to 118° C. for concentrated crystallization. When more crystals appear, heating is stopped, stirring and cooling are performed for crystallization. When the temperature drops to 31° C., the solution is allowed to stand for 30 minutes and then filtered. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, and scandium chloride hexahydrate crystals are obtained.

[0046] Step 1.4: Take analytical pure ammonium carbonate and add high-purity water to dissolve it. After dissolving to a mass fraction of 16.8%, filter it and control the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.2ppm to obtain an ammonium carbonate solution for standby use;

[0047] Step 1.5: After dissolving the scandium chloride hexahydrate crystals obtained in step 1.3 into a scandium chloride solution with a mass fraction of 16.5% with high-purity water, slowly add the solution to the ammonium carbonate solution obtained in step 1.4 under stirring, keep warm and stir at 80° C. for 1 hour, filter, wash with water, control the chlorine content to be less than 50 ppm, and the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.5 ppm, to obtain active high-purity scandium carbonate;

[0048] Step 2, preparing scandium metaphosphate;

[0049] Step 2.1 Take 85% food-grade phosphoric acid by mass, add high-purity water to dilute it to a mass fraction of 22%, add the high-purity scandium carbonate obtained in step 1.5, the molar ratio of phosphoric acid to scandium carbonate is 3.3:1, heat to 60°C for insulation reaction for 40 minutes, then heat to 115°C for concentration and crystallization, stop heating when concentrating to sugar-like crystals, continue stirring to cool and crystallize, cool to 37°C, and then stand for about 30 minutes, at which time the ratio of supernatant to crystals is 1:8-10, filter to obtain scandium dihydrogen phosphate crystals;

[0050] Step 2.2 Add the scandium dihydrogen phosphate crystals obtained in step 2.1 to a tetrafluoro beaker and dry at 220°C. Foaming will occur during the drying period. When the foaming hardens, continue to dry at 220°C for 1.5 hours. Add the foamed scandium dihydrogen phosphate to a quartz crucible and heat it to 580°C for high-temperature treatment for 2.5 hours. The iron content is 1.5ppm, and the target product is obtained. XRD detection is qualitatively scandium metaphosphate. After testing, the content of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the product is less than 1ppm, the loss on ignition is 0.39%, and the purity is greater than 99.9%.

[0051] Example 3

[0052] In this embodiment, scandium metaphosphate is prepared by the following steps

[0053] Step 1, preparing active scandium salt;

[0054] Step 1.1: Take analytical pure hydrochloric acid and place it in a glass beaker, add high-purity water to dilute it into a hydrochloric acid solution with a mass fraction of 12%, and then add scandium chloride hexahydrate to the diluted hydrochloric acid solution to dissolve it. The mass ratio of the hydrochloric acid solution to the scandium chloride hexahydrate is 4:1, and a scandium chloride solution is obtained;

[0055] Step 1.2: filtering the scandium chloride solution through a filter with a precision of 1 μm to remove insoluble matter and mechanical impurities therein to obtain a relatively pure scandium chloride solution;

[0056] Step 1.3: The scandium chloride solution obtained in step 1.2 is heated to 120° C. for concentrated crystallization. When more crystals appear, heating is stopped, and the solution is stirred and cooled for crystallization. When the temperature drops to 40° C., the solution is allowed to stand for 50 minutes and then filtered. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, and scandium chloride hexahydrate crystals are obtained.

[0057] Step 1.4: Take analytical pure ammonium carbonate and add high-purity water to dissolve it. After dissolving to a mass fraction of 18%, filter it and control the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.2ppm to obtain an ammonium carbonate solution for standby use;

[0058] Step 1.5: After dissolving the scandium chloride hexahydrate crystals obtained in step 1.3 into a scandium chloride solution with a mass fraction of 18% with high-purity water, slowly add it to the ammonium carbonate solution obtained in step 1.4 under stirring, keep warm and stir at 75° C. for 2 hours, filter, wash with water, control the chlorine content to less than 50 ppm, and the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to less than 0.5 ppm, to obtain active high-purity scandium carbonate;

[0059] Step 2, preparing scandium metaphosphate;

[0060] Step 2.1 Take 85% food-grade phosphoric acid by mass, add high-purity water to dilute it to a mass fraction of 25%, add the high-purity scandium carbonate obtained in step 1.5, the molar ratio of phosphoric acid to scandium carbonate is 3.5:1, heat to 80°C for insulation reaction for 35 minutes, then heat to 120°C for concentration and crystallization, stop heating when concentrating to sugar-like crystals, continue stirring to cool and crystallize, cool to 40°C, and then stand for about 30 minutes, at which time the ratio of supernatant to crystals is 1:8-10, filter to obtain scandium dihydrogen phosphate crystals;

[0061] Step 2.2 Add the scandium dihydrogen phosphate crystals obtained in step 2.1 to a tetrafluoro beaker and dry at 250°C. Foaming will occur during the drying period. When the foaming hardens, continue to dry at 250°C for 1 hour, then add the foamed scandium dihydrogen phosphate to a quartz crucible and heat it to 600°C for high-temperature treatment for 2 hours. The iron content is 1.8ppm, and the target product is obtained. XRD detection is qualitatively scandium metaphosphate. After testing, the content of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the product is less than 1ppm, the loss on ignition is 0.41%, and the purity is greater than 99.9%.

[0062] Example 4

[0063] In this embodiment, scandium metaphosphate is prepared by the following steps

[0064] Step 1, preparing active scandium salt;

[0065] Step 1.1: Take analytical pure hydrochloric acid and place it in a glass beaker, add high-purity water to dilute it into a hydrochloric acid solution with a mass fraction of 11%, and then add scandium chloride hexahydrate to the diluted hydrochloric acid solution to dissolve it. The mass ratio of the hydrochloric acid solution to the scandium chloride hexahydrate is 6:1, and a scandium chloride solution is obtained;

[0066] Step 1.2: filtering the scandium chloride solution through a filter with a precision of 1 μm to remove insoluble matter and mechanical impurities therein to obtain a relatively pure scandium chloride solution;

[0067] Step 1.3: The scandium chloride solution obtained in step 1.2 is heated to 110° C. for concentrated crystallization. When more crystals appear, heating is stopped, and the solution is stirred and cooled for crystallization. When the temperature drops to 30° C., the solution is allowed to stand for 60 minutes and then filtered. The contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium are all controlled to be less than 0.2 ppm, and scandium chloride hexahydrate crystals are obtained.

[0068] Step 1.4: Take analytical pure ammonium carbonate and add high-purity water to dissolve it. After dissolving to a mass fraction of 15%, filter it and control the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.2ppm to obtain an ammonium carbonate solution for standby use.

[0069] Step 1.5: After dissolving the scandium chloride hexahydrate crystals obtained in step 1.3 into a scandium chloride solution with a mass fraction of 15% with high-purity water, slowly add it to the ammonium carbonate solution obtained in step 1.4 under stirring, keep warm and stir for aging at 72° C. for 1 hour, filter, wash with water, control the chlorine content to be less than 50 ppm, and the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium to be less than 0.5 ppm, to obtain active high-purity scandium carbonate;

[0070] Step 2, preparing scandium metaphosphate;

[0071] Step 2.1 Take 85% food-grade phosphoric acid by mass, add high-purity water to dilute it to a mass fraction of 25%, add the high-purity scandium carbonate obtained in step 1.5, the molar ratio of phosphoric acid to scandium carbonate is 3.2:1, heat to 65°C for insulation reaction for 60 minutes, then heat to 112°C for concentration and crystallization, stop heating when concentrating until sugar-like crystals appear, continue stirring to cool and crystallize, cool to 30°C, and then stand for about 30 minutes. When the ratio of supernatant to crystals is 1:8-10, filter to obtain scandium dihydrogen phosphate crystals;

[0072] Step 2.2 Add the scandium dihydrogen phosphate crystals obtained in step 2.1 to a tetrafluoro beaker and dry at 210°C. Foaming will occur during the drying period. When the foaming hardens, continue to dry at 210°C for 1 hour. Add the foamed scandium dihydrogen phosphate to a quartz crucible and heat it to 500°C for high-temperature treatment for 3 hours. The iron content is 1.7ppm, and the target product is obtained. XRD detection is qualitatively scandium metaphosphate. After testing, the content of cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the product is less than 1ppm, the loss on ignition is 0.4%, and the purity is greater than 99.9%.

Claims

1. A method for preparing optical grade scandium metaphosphate, characterized in that: The following steps are involved: Step 1, preparing high-purity scandium carbonate; Step 1.1: dilute analytical pure hydrochloric acid with pure water / high-purity water to a hydrochloric acid solution with a mass fraction of 10-15%, and then add scandium chloride hexahydrate thereto to dissolve it, wherein the mass ratio of the diluted hydrochloric acid solution to scandium chloride hexahydrate is 4-6:1, to obtain a scandium chloride solution; Step 1.2: filtering the scandium chloride solution to remove insoluble matter and mechanical impurities to obtain a relatively pure scandium chloride solution; Step 1.3: Recrystallize the scandium chloride solution obtained in step 1.2, and control the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium to be less than 0.2 ppm, to obtain scandium chloride hexahydrate crystals; Step 1.4: dissolving analytically pure ammonium carbonate into a 15-18% by mass ammonium carbonate solution with pure water / high-purity water, filtering, and controlling the contents of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium in the ammonium carbonate solution to be less than 0.2 ppm; Step 1.5: After dissolving the scandium chloride hexahydrate crystals obtained in step 1.3 into a scandium chloride solution with a mass fraction of 15-18% with pure water / high-purity water, the solution is slowly added to the ammonium carbonate solution obtained in step 1.4 under stirring, and then the solution is heat-insulated and aged, filtered, and washed with water. The chlorine content is controlled to be less than 50 ppm, and the content of iron, cobalt, nickel, copper, titanium, vanadium, cadmium, and chromium is controlled to be less than 0.5 ppm, so as to obtain active high-purity scandium carbonate; Step 2, preparing scandium metaphosphate; Step 2.1: using 20-25% by mass of food-grade phosphoric acid and the active high-purity scandium carbonate to react with heat preservation and stirring, concentrating and crystallizing, filtering, and obtaining scandium dihydrogen phosphate crystals; Step 2.2: Dry the scandium dihydrogen phosphate crystals at 200-250°C. Foaming will occur during the drying process. After the foaming hardens, continue drying at 200-250°C for 1-2 hours. Heat the foamed scandium dihydrogen phosphate to 500-600°C for high-temperature treatment for 2-3 hours to obtain scandium metaphosphate.

2. The method for preparing optical grade scandium metaphosphate according to claim 1, characterized in that: In step 1.2, the scandium chloride solution is filtered using a filter with a filtration accuracy of at least 1 μm.

3. The method for preparing optical grade scandium metaphosphate according to claim 1, characterized in that: The specific method of step 1.3 is: heating the scandium chloride solution obtained in step 1.2 to 110-120°C for concentrated crystallization, stopping heating when more crystals appear, stirring and cooling to crystallize, and when the temperature drops to 30-40°C, standing for 30-60 minutes and then filtering, and the iron, cobalt, nickel, copper, titanium, vanadium, cadmium and chromium contents are all controlled to be less than 0.2ppm, to obtain scandium chloride hexahydrate crystals.

4. The method for preparing optical grade scandium metaphosphate according to any one of claims 1 to 3, characterized in that: In step 1.5, the mixture is kept at 70-80° C. and stirred for aging for 1-2 hours.

5. The method for preparing optical grade scandium metaphosphate according to claim 4, characterized in that: Step 2.1 is specifically as follows: dilute food-grade phosphoric acid with pure water / high-purity water to a mass fraction of 20-25%, add the active high-purity scandium carbonate thereto, the molar ratio of phosphoric acid to scandium carbonate is 3.1-3.5:1, stir and react at 60-80°C for 30-60 minutes, then heat to 110-120°C for concentrated crystallization, stop heating when sugar-like crystals appear, continue stirring to cool and crystallize, cool to 30-40°C, let stand until the ratio of supernatant to crystals is 1:8-10, filter, and obtain scandium dihydrogen phosphate crystals.

6. An optical grade scandium metaphosphate, characterized in that: The method is prepared by any one of claims 1 to 5.

7. An optical glass, characterized in that: The optical grade scandium metaphosphate described in claim 7 is used as an additive.